2022
DOI: 10.3390/ijerph19074347
|View full text |Cite
|
Sign up to set email alerts
|

The Portrait of Cyberchondria—A Cross-Sectional Online Study on Factors Related to Health Anxiety and Cyberchondria in Polish Population during SARS-CoV-2 Pandemic

Abstract: The SARS-CoV-2 pandemic has served as a magnifying glass for cyberchondria, while the internet emerged as one of the main sources of medical information and support. The core ambition of this study was to estimate the level of cyberchondria and describe the socio-demographic, clinical and pandemic-related factors affecting its severity amid the SARS-CoV-2 pandemic. A cross-sectional study was performed between 16 May 2020 and 29 December 2020 in Poland within a sample of 538 adult internet users. The online su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…In contrast, Ciułkowicz et al . [ 36 ] reported that occupational inactivity results in limited access to healthcare, which in turn creates an economic burden on these individuals. A possible explanation for this difference is that in Saudi Arabia, citizens are provided healthcare for free, and thus it has a fair coverage for those non-working, while the pension for retirees adequately covers any additional healthcare needs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ciułkowicz et al . [ 36 ] reported that occupational inactivity results in limited access to healthcare, which in turn creates an economic burden on these individuals. A possible explanation for this difference is that in Saudi Arabia, citizens are provided healthcare for free, and thus it has a fair coverage for those non-working, while the pension for retirees adequately covers any additional healthcare needs.…”
Section: Discussionmentioning
confidence: 99%
“…Cyberchondria have a negative impact on nursing students. It can lead to heightened anxiety, stress, and even hypochondria (9). This can affect their ability to focus on their studies and perform effectively in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…After the early pandemic phases, the acute stress factor gained chronic character leading to a novel manifestation of pandemic-associated mental disorders. Currently, many researchers report on factors contributing or correlated with mental health outcomes in the general population, in students, or in medical professionals [ 11 , 12 , 13 , 14 ]. However, much less is known about the consequences of COVID-19-related psychological strain on vulnerable populations, such as individuals at risk for mental disorders, the elderly, and those frequently requiring services of the health care system—patients treated for chronic diseases, such as neurological disorders, dermatological conditions, or patients undergoing dialyses.…”
Section: Introductionmentioning
confidence: 99%